Cascaded Metasurface Interferometer for Multipath Interference with Classical and Quantum Light - Aschwanden, Rebecca; Claro-Rodríguez, Nicolás; Zhao, Ruizhe; Kallert, Patricia Anna Maria; Krieger, Tobias; Buchinger, Quirin; Covre da Silva, Saimon F.; Stroj, Sandra; Rota, Michele; Höfling, Sven; Huber-Loyola, Tobias; Rastelli, Armando; et al. (ACS Photonics)
Beamsplitters represent fundamental components in both classical and quantum optical systems, enabling the distribution of light, as well as the generation of interference, superposition, and entanglement. However, optical networks constructed from conventional bulk 2 × 2-beamsplitters encounter inherent scalability issues, as the number of required beamsplitters scales quadratically with the number of optical modes for a fully connected network. Metasurfaces offer a promising route to overcome these constraints. By manipulating light at the wavelength scale, compact optical components with advanced functionalities can be constructed, which address several modes simultaneously. In this work, we design and experimentally utilize a metasurface as a multiport beamsplitter. Furthermore, we realized a multimode interferometer composed of two cascaded metasurfaces. We characterize the individual and cascaded metasurfaces by using classical light, showing controllable splitting ratios through tunable phase relations. We then expand the approach to quantum light, employing single photons to demonstrate second- and third-order photon correlations as well as single photon interference across multiple spatial paths. These results establish metasurface-based multiport beamsplitters as a scalable and reconfigurable platform bridging classical and quantum photonics.
Keywords: metasurface; beamsplitter; interferometer; quantum network; single photons; nanophotonics

Polarization- and Wave-Vector Selective Optical Metasurface with Near-Field Coupling - Wetter, Helene; Wingenbach, Jan; Rehberg, Falk; Gao, Wenlong; Schumacher, Stefan; Zentgraf, Thomas (ACS Photonics)
Metasurfaces are powerful tools for manipulating light using small structures on the nanoscale. In most metasurfaces, near-field couplings are treated as being unfavorable perturbations. Here, we experimentally investigate a structure consisting of sinusoidally modulated silicon waveguides where near-field coupling of local resonances leads to negative coupling, i.e., a negative coupling constant. This gives rise to wave-vector-dependent eigenstates of elliptical, linear, and circular polarizations. In particular, fully circular polarization states are not only present at a single point in momentum space (k-space) but also along a line. This circular polarization line, as well as a linear polarization line, emanates from a polarization degeneracy at the Dirac point. We experimentally validate the existence of these eigenstates and demonstrate the energy-, polarization-, and wave vector dependence of this metasurface as well as its sensitivity to fabrication tolerances. By tuning the incident k-vector, certain polarization-energy eigenstates are strongly reflected, allowing for uses in angle-tunable polarization filters and light sources.
Keywords: metasurface; waveguides; Dirac point; polarization; negative coupling

A gradient-damage model for amorphous glassy polymers: Consistent formulation of viscoplasticity and damage evolution in a micromorphic framework - Hamdoun, Ayoub; Mahnken, Rolf; Ostwald, Richard (European Journal of Mechanics / A Solids)

A Simpler Exponential-Time Approximation Algorithm for MAX-k-SAT - Buhrman, Harry; Gharibian, Sevag; Landau, Zeph; Gall, François Le; Schuch, Norbert; Tamaki, Suguru (SIAM Symposium on Simplicity in Algorithms (SOSA))
We present an extremely simple polynomial-space exponential-time $(1-ε)$-approximation algorithm for MAX-k-SAT that is (slightly) faster than the previous known polynomial-space $(1-ε)$-approximation algorithms by Hirsch (Discrete Applied Mathematics, 2003) and Escoffier, Paschos and Tourniaire (Theoretical Computer Science, 2014). Our algorithm repeatedly samples an assignment uniformly at random until finding an assignment that satisfies a large enough fraction of clauses. Surprisingly, we can show the efficiency of this simpler approach by proving that in any instance of MAX-k-SAT (or more generally any instance of MAXCSP), an exponential number of assignments satisfy a fraction of clauses close to the optimal value.

Is flipped classroom really superior?—Questioning the flip in K-12 teaching - Wiesner, Patrick; Krauss, Stefan; Stegmüller, Nathalie; Binder, Karin (Frontiers in Education)
There is a contradiction between seven meta-analyses, all of which indicate a substantial benefit of the flipped classroom (FC) method for K-12 teaching and some larger study that found no such benefit when compared to “traditional” teaching. In the theoretical part of the paper, we shed light on this contradiction by consulting general literature on meta-analyses. Ranking the 50 included FC studies by the number of classes per experimental condition, we found a negative correlation between the “size” of a study and the effect in favor of FC. In the empirical part, we present an FC study with three conditions concerning mathematical teaching, based on n = 950 students aged 11–13, in which many relevant covariates (e.g., quality of instruction) were addressed. One FC condition was based on students’ knowledge acquisition through instructional videos at home (FCn: n = 12 classes). Considering that self-regulation support might play a crucial role especially for young students working at home, another FC condition (FCS: n = 12 classes) was implemented, in which students could learn additional math-free strategies concerning watching instructional videos. Both FC-conditions were experimentally compared with a control group of traditional teaching (TT: n = 13 classes). No significant effect on learning gains was found between FCn and TT, indicating that “flipping” alone may not be more effective per se. However, a significant difference was found between FCS and FCn. Thus, supporting students’ self-regulation in addition may in indeed open the door to successful FC, even with very young students.

14th IASE Satellite Conference "Statistics and Data Science Education in STEAM"

Effects of a simulation-based training on students conceptual understanding of the Binomial test - Binder, Karin; Schnaitmann, Stephan; Erickson, Tim (Proceedings of the IASE 2025 Satellite Conference - Statistics and Data Science Education in STEAM)

Images of Climate Crises. Critical Remarks on Climate-Technical Imagery Production and the Possibilities of Desirable Futures - Henschen, Patrick; Töpfer, Lew (ffk Journal)

Erziehungswissenschaftliche Perspektiven auf Familie und ihre Öffentlichkeit(en). Bericht zur Tagung des Netzwerks Erziehungswissenschaftliche Familienforschung (EWIFF) „Familie und ihre Öffentlichkeit(en)“ von 7. bis 8. Juni an der Universität Erfurt. - Reichenbach, Alexandra Maria; Jäde, Sylvia (ZSE (Zeitschrift für Soziologie der Erziehung und Sozialisation))
Die Bonner Ethik-Erklärung/Über Künstliche Intelligenzen, Bildung und Subjektwerdung/Tagungsberichte

Prädiktoren der persönlichen Verpflichtung in Eltern-Kind-Beziehungen im Erwachsenenalter - Schönert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie)

Untersuchung der Einflussfaktoren auf die Recyclingfähigkeit von flammgeschütztem Polyamid 12-Pulver beim selektiven Lasersintern (Studienarbeit) - Hüwel, Fabian

Towards Single‐Crystalline DNA Origami Lattices on Silicon Wafers for Bottom‐Up Nanofabrication - Järvinen, Heini; Parikka, Johannes M.; Rajapaksha, R. P. Thiwangi N.; Keller, Adrian Clemens; Toppari, J. Jussi (Small Structures)
In recent years, nanostructures assembled by DNA have found promising applications in optics, medicine, and sensing. DNA origami in particular provides unique self‐assembly properties, not only enabling a vast variety of functionalization schemes but also presenting a promising route to fabricate large‐scale, bottom‐up nanostructured arrays. This approach has comparable precision to electron beam lithography but avoids slow and expensive patterning steps. However, self‐assembly of lattices with high order and well‐defined periodicity requires careful tuning of the deposition parameters and interactions involved, which has been done mostly on mica so far. As mica is not compatible with standard microfabrication processes, we investigate here the assembly of DNA origami lattices on the most general microfabrication material, that is, silicon wafers, which has turned out to be rather challenging. We study how the forming of polycrystalline 2D‐fishnet‐type lattices is influenced by different incubation conditions and strengths of the origami–origami and origami‐surface interactions, with the aim to create large‐scale single‐crystalline lattices. The lattices are characterized by atomic force microscopy and analyzed for precision of formation, achievable domain size, and surface coverage of well‐formed lattices. Thanks to the silicon substrate, these DNA origami lattices can be further combined with traditional microfabrication processes to turn them, for example, into metamaterials with novel optical properties.

Discrete Diffusion-Based Model-Level Explanation of Heterogeneous GNNs with Node Features - Das, Pallabee; Heindorf, Stefan (Proceedings of the ACM Web Conference 2026 (WWW ’26))
Many real-world datasets, such as citation networks, social networks, and molecular structures, are naturally represented as heterogeneous graphs, where nodes belong to different types and have additional features. For example, in a citation network, nodes representing "Paper" or "Author" may include attributes like keywords or affiliations. A critical machine learning task on these graphs is node classification, which is useful for applications such as fake news detection, corporate risk assessment, and molecular property prediction. Although Heterogeneous Graph Neural Networks (HGNNs) perform well in these contexts, their predictions remain opaque. Existing post-hoc explanation methods lack support for actual node features beyond one-hot encoding of node type and often fail to generate realistic, faithful explanations. To address these gaps, we propose DiGNNExplainer, a model-level explanation approach that synthesizes heterogeneous graphs with realistic node features via discrete denoising diffusion. In particular, we generate realistic discrete features (e.g., bag-of-words features) using diffusion models within a discrete space, whereas previous approaches are limited to continuous spaces. We evaluate our approach on multiple datasets and show that DiGNNExplainer produces explanations that are realistic and faithful to the model's decision-making, outperforming state-of-the-art methods.

Simulation-based process chain for aluminum clinched joints: Predicting geometry, strength, and failure behavior - Mergheim, Julia; Wallmersperger, Thomas; Wolf, Eugen; Schlichter, Malte; Ludwig, Jean-Patrick; Friedlein, Johannes; Gerritzen, Johannes; Devulapally, Deekshith Reddy; Chen, Chin; Weiss, Deborah; Krome, Sven; Reschke, Gregor; et al. (Journal of Advanced Joining Processes)

Common Foundations for Recursive Shape Languages - Okulmus, Cem; Ahmetaj, Shqiponja; Boneva, Iovka; Hidders, Jan; Jakubowski, Maxime; Labra Gayo, José Emilio; Martens, Wim; Mogavero, Fabio; Murlak, Filip; Savković, Ognjen; Šimkus, Mantas; Tomaszuk, Dominik (Proceedings of the 23rd International Conference on Principles of Knowledge Representation and Reasoning (KR 2026))

From mismatch to synergy: how new ventures and family-owned firms navigate cooperation - Kundisch, Dennis; Wilms, Alexander (Journal of Small Business and Enterprise Development)

Single-surface and double-surface plasticity for micropolar continuum - Börger, Alexander; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract The micropolar continuum is a special case of a micromorphic material model and has additional degrees of freedom in the form of microrotations compared to the classical continuum. With the micropolar model, size effects can be considered and the boundary value problem can be regularized when localization effects occur. In order to map the microrotations, an additional strain measure and an additional stress are introduced. For simulation of plasticity, it is possible to define one yield function, and thus one plastic multiplier as well as one equivalent plastic strain occur. This approach is known as the single-surface plasticity approach. The macro- and micro-stresses are coupled in a common flow function. On the other hand, there is the so-called double-surface plasticity when one yield function, one plastic multiplier, and one equivalent plastic strain, respectively, are introduced for each of the macro- and micro-variables. The coupling of the macro- and micro-variables is established by a possible coupling of both yield functions. The purpose of this paper is to compare both approaches and to identify similarities and differences.

Coxeter-Dynkin algebras of canonical type - Perniok, Daniel (Journal of Pure and Applied Algebra)
We propose a definition of Coxeter-Dynkin algebras of canonical type generalising the definition as a path algebra of a quiver. Moreover, we construct two tilting objects over the squid algebra - one via generalised APR-tilting and one via one-point-extensions and reflection functors - and identify their endomorphism algebras with the Coxeter-Dynkin algebra. This shows that our definition gives another representative in the derived equivalence class of the squid algebra, and hence of the corresponding canonical algebra. Finally, we have a closer look at the Grothendieck group and the Euler form which illustrates the connection to Saito's classification of marked extended affine root systems. On the other hand, this enables us to prove that in the domestic case Coxeter-Dynkin algebras are of finite representation type.

Navigating the dual nature: do explainers adapt to explainee interests when explaining technical artifacts - Lutz, Terfloth; Buhl, Heike M.; Lohmer, Vivien; Kern, Friederike; Schaffer, Michael E.; Schulte, Carsten (International Journal of Technology and Design Education)

Document-level Relation Extraction using Reinforcement Learning with Knowledge Graph Feedback - Manzoor, Ali; Zahera, Hammada M.; Saleem, Muhammad; Mahmood, Yasir; Speck, René; Khan, Hashim; Ngonga Ngomo, Axel-Cyrille (The Semantic Web – 23rd European Semantic Web Conference, ESWC 2026, Dubrovnik , Croatia, May 10-14, 2026, Proceedings)
Keywords: dice hamada hashim kiakadamie mahmood manzoor ngonga rene sail saleem